(untitled) (Research, Society and Development, 2021)
The aim of the study is to understand the Systematization of Nursing Care (NCS), based on the daily lives of nurses who perform their actions at the Psychosocial Care Center (CAPS). This is a qualitative study, based on field research supported by the theoretical and methodological framework of Comprehensive Sociology by Michel Maffesoli, which has daily life as the place where everything happens, where being together is capable of mobilizing experiences to a sensible reason. Eleven nurses working in CAPS administered exclusively by a municipality in the Zona da Mata Mineira were interviewed. Results and discussions: three categories emerged: NCS in the daily practice; the interactionist NCS; and existential NCS in their knowledge. These deal with systematized nursing practices entangled by the National Mental Health Policy (PNSM), show that the nurse-user encounter is at the heart of the NCS and reflects on the need to reframe knowledge to improve care. Conclusion: the study provides for solving doubts related to the performance of nursing in mental health and contributes to reflect on the construction of their knowledge in order to strengthen care in order to favor paths to autonomy and professional recognition.